Aplikace strukturální analýzy na japonský mýtus - Andrea Beláňová (AntropoWebzin)
The article reflects using of famous structural analysis of Claude Lévi-Strauss on an old Japanese myth of Amaterasu and Susanoo which refers to the „disappearance of the sun“. French scholar left a monumental work which is a big challenge for every student of anthropology and all cultural studies. His specific way of analyzing the myth searches for the universal structure of human thinking. Lévi-Strauss focused especially on the myths of North American Indians where his theory works quite perfectly. What happens if we try to apply his approach on a myth from the cultural area which is absolutely different? Can this view bring something new? And what does it tell about Lévi-Strauss´s method itself?